INTEGRATED QUALITY MANAGEMENT (TOTAL QUALITY MANAGEMENT) IN THE CONTEXT OF EDUCATION - Finy Muslihatuzzahro (STIT PRINGSEWU, 2023)
Education is a form of embodiment of human culture that is dynamic and full of developments. Therefore, changes or developments in education are things that should happen in line with changes in the culture of life. The method in this study uses qualitative research, with a literature study approach and is descriptive-analytical, data analysis this time through the data reduction stage, namely selection, concentration of discussion, abstraction of the entire grand data to several selected data needed. The results of this study show that Integrated Quality Management is an approach in running a business that tries to maximize the competitiveness of the organization through continuous improvement to products, people, services, processes and the environment. As for the differences between quality and non-quality organizations, of course, there are inequalities when viewed from the table that has been presented, such as in terms of vision and mission and strategy. MMT is a concept referring to quality that is useful for satisfying its customers. In the context of education, an educational institution is said to be of high quality if internal and external customers have established satisfaction with the services provided. In order to ensure the management of services that are able to produce quality output. Based on the description above, it is very beautiful if every management in an educational institution is based on MMT which basically emphasizes continuous improvement and customer satisfaction to produce quality education.